Modeling the impact of changes in tobacco use on individual disease risks. (13th November 2019) - Djurdjevic, S; Baker, G
Abstract: : Philip Morris International has developed a Population Health Impact Model (PHIM) to estimate the effects of marketing Reduced-Risk Products on population health. The PHIM creates a disease-specific risk profile for each individual based on their age and smoking history. To create a risk profile, the PHIM calculates, at each year of age, the excess relative risk (ERR=relative risk [RR]-1) by multiplying an individual's equivalent dose (ED) by the ERR for smoking vs. never smoking. ED is defined as 0 at birth and stays at 0 while the individual is a non-smoker. Once tobacco use starts, the individual's ED rises toward the relative exposure (RE) corresponding to the product used. Following quitting or change of product, ED moves toward the new value of RE. The model uses estimates of age- and disease-specific current smoking RRs and ERR half-lives following cessation, derived from meta-analyses of published data. Estimates of the half-life of excess risk are also used when estimating rise in ERR following initiation or change in ERR following a change in product use. We apply the method to data for the four main smoking-related diseases; lung cancer, ischemic heart disease, stroke, and chronic obstructive pulmonary disease. For a given disease and age group, the PHIM can derive estimates of the average ERR for each individual in the population studied. Given an overall estimate of absolute population risk, the PHIM can then also be used to derive estimates of absolute risk for each individual. Key messages: Health impact modeling can be used to understand the individual and population impacts of introducing reduced risk tobacco products. Footnote: *Reduced-Risk Products are products that present, are likely to present, or have the potential to present less risk of harm to smokers who switch to these products vs continued smoking.